2005
DOI: 10.1056/nejmsr043743
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Decline in Life Expectancy in the United States in the 21st Century

Abstract: Forecasts of life expectancy are an important component of public policy that influence age-based entitlement programs such as Social Security and Medicare. Although the Social Security Administration recently raised its estimates of how long Americans are going to live in the 21st century, current trends in obesity in the United States suggest that these estimates may not be accurate. From our analysis of the effect of obesity on longevity, we conclude that the steady rise in life expectancy during the past t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
1,269
1
54

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,323 publications
(1,361 citation statements)
references
References 40 publications
12
1,269
1
54
Order By: Relevance
“…Globally, the prevalence of overweight and obesity has risen at an alarming rate over the past two decades, with over two billion people now meeting the definition of these two categories 1. From a public health standpoint, it is believed that the prevailing obesity trends in the USA may have the net effect of decreasing life expectancy trends 2. Numerous studies have shown a clear relationship between obesity and risk of developing cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the prevalence of overweight and obesity has risen at an alarming rate over the past two decades, with over two billion people now meeting the definition of these two categories 1. From a public health standpoint, it is believed that the prevailing obesity trends in the USA may have the net effect of decreasing life expectancy trends 2. Numerous studies have shown a clear relationship between obesity and risk of developing cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…A steady linear growth of life expectancy to an undetermined biological limit was hypothesized in this study. However, other studies have considerably different aspects and factors limiting duration of life [2] and have even forecasted a declining life expectancy due to factors such as the consequences of the increased prevalence of obesity [3]. Moreover, the prevalence of diseases such as cancer or dementia, all with negative consequences, is clearly increasing because of longevity in our populations.…”
Section: Introductionmentioning
confidence: 99%
“…10 Unless this trend is curtailed, obesity-related disease, disability and death worldwide is projected to increase well into the 21st century, 15 whereas life expectancy at birth and at older ages may begin to decline by the middle of the 21st century. 16 Fundamentally, the etiology of overweight in children and adolescents, as in adults, is attributable to energy (caloric) intake in excess of energy expenditure. Genetic, environmental, socio-cultural, and family characteristics have been identified as key influences on energy expenditure and dietary intake, and subsequent overweight prevalence.…”
Section: Introductionmentioning
confidence: 99%